Go Digital: Optimalisasi Citra Produk dan Pemasaran Digital untuk Meningkatkan Volume Penjualan Produk Kerupuk Beras Ibu Rumah Tangga Dusun Dayu - Shinta Nastitie Komalasari; Gustita Arnawati P; Made Wedaswari; Ahmad Dzakiyyudin; Yoga Pratama Nugroho; Hesiya May Ghaisani (Jurnal Pengabdian Masyarakat, 2026)
The availability of resources and the potential for an independent community will not automatically improve community self-reliance if they are not supported by adequate knowledge and the ability to utilize technological advancements. Therefore, this community service activity was conducted to provide training on the use of technology and the accessibility of social media in order to optimize existing resources and local potential. In Dayu Village, the abundant rice resources are utilized by a group of housewives to produce healthy snacks in the form of rice crackers. This activity aims to strengthen the economic independence of the community through the application of digital branding and digital marketing strategies. By combining local resource potential with knowledge and skills in utilizing digital media, the housewives were able to improve the promotion and marketing of their products more effectively. The results of this activity indicate that the training on digital branding and digital marketing contributed positively to increasing rice cracker sales and enhancing the independence and productivity of the housewives in Dayu village. Thus, the use of technology-based marketing strategies can become an effective approach in supporting community empowerment and sustainable local economic development.